An experimental investigation of the impact of critical and warm comments on state paranoia in a non-clinical sample. (March 2019) - Butler, Rebecca; Berry, Katherine; Ellett, Lyn; Bucci, Sandra
Abstract: Background and objectives: Interpersonal stress is key to the development and maintenance of paranoia. Much attention has been given to the impact of interpersonal stressors, such as criticism, on outcomes in psychosis. Less attention has been given to the potentially protective effects of positive interpersonal factors. This study tested experimentally whether criticism and warm comments elicited changes in state paranoia. Whether warm comments provided protective effects when participants faced subsequent social exclusion was also examined. Method: A nonclinical sample (N = 97) was randomised to criticism, warm comments, or neutral comments conditions. Participants then played a virtual ball game (Cyberball), during which they were systematically excluded from the game. State paranoia was measured before and after the affective stimuli and after social exclusion. Self-esteem and trait paranoia were also measured. Results: Paranoia levels increased following exposure to criticism ( p  = .011). Paranoia was not significantly lower following exposure to warm comments ( p  = .203). Warm comments did not provide protection against the effects of subsequent social exclusion. The warm comments condition was the only condition in which significant increases in paranoia were seen following social exclusion ( p  = .004). Limitations: Use of a non-clinical sample limits generalisation to clinical populations. Conclusions: Criticism is sufficient to elicit increases in paranoia in non-clinical participants. Warm comments are insufficient to significantly reduce paranoia or provide protective effects against subsequent negative interpersonal experiences, highlighting the need to balance therapeutic warmth with amelioration of social stressors in paranoia. Highlights: Paranoia levels increased following exposure to criticism. Warmth is insufficient to reduce paranoia and negative interpersonal experiences. The warmth condition significantly increased paranoia following social exclusion. Criticism was not associated with change in self-esteem, even after social exclusion. Warmth increased self-esteem which decreased when participants faced social exclusion.